Dragon in a three-piece suit : the emergence of capitalism in China - Guthrie, Doug, 1969- (Princeton University Press, 1999)
"Dragon in a Three-Piece Suit is sociological examination of what is perhaps the main engine of economic reform in China, the large industrial firm. Doug Guthrie, who spent more than a year in Shanghai studying firms, interviewing managers, and gathering data on firms' performance and practices, provides the first detailed account of how these firms have been radically transformed since the mid-1980s."--Jacket.